Measuring rice yield from space the case of Thai Binh province, Vietnam. - Guan,Kaiyu (Economics Working Papers., 2018)
Traditional methods for estimating rice yield rely on field data, which are time-consuming and expensive to collect. Significant cloud coverage in Southeast Asia limits the availability of cloud-free satellite images to serve as an alternative to field data. This paper presents an innovative data fusion technique which combines two freely available sources of satellite data for Thai Binh, Viet Nam. Results show that data fusion increases the spatial and temporal availability of satellite data and allows for estimating the best empirical relationship between satellite derived yield indexes and field-based yield data.